2021
DOI: 10.12688/wellcomeopenres.16616.1
|View full text |Cite
|
Sign up to set email alerts
|

The Avon Longitudinal Study of Parents and Children - A resource for COVID-19 research: Home-based antibody testing results, October 2020

Abstract: The Avon Longitudinal Study of Parents and Children (ALSPAC) is a prospective population-based cohort study which recruited pregnant women in 1990-1992 and has followed these women, their partners (Generation 0; G0) and offspring (Generation 1; G1) ever since. The study reacted rapidly to the COVID-19 pandemic, deploying online questionnaires in March and May 2020. Home-based antibody tests and a further questionnaire were sent to 5220 participants during a two-week period of October 2020. 4.2% (n=201) of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
(28 reference statements)
0
27
0
Order By: Relevance
“…Additional linkage data -such as from Public Health England COVID-19 testing data -or data from other sources is required to answer such questions 39 . For instance, recent research using ALSPAC COVID-19 serology test data demonstrates that individuals consenting to have a COVID-19 antibody test were more likely to report having had COVID-19 23 . Questionnaire completion may have been similarly biased, thus increasing the risk of selection bias in studies where COVID-19-related outcomes are the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional linkage data -such as from Public Health England COVID-19 testing data -or data from other sources is required to answer such questions 39 . For instance, recent research using ALSPAC COVID-19 serology test data demonstrates that individuals consenting to have a COVID-19 antibody test were more likely to report having had COVID-19 23 . Questionnaire completion may have been similarly biased, thus increasing the risk of selection bias in studies where COVID-19-related outcomes are the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Since the start of the pandemic, participants have been sent four online COVID-19 questionnaires to assess diagnoses, symptoms, and behavioural and environmental factors related to COVID-19, and the impact of the pandemic on health 19,20,23,24 . Questionnaires were sent to all participants who had not withdrawn from the study or declined to participate in questionnaires, and had a valid email address in the ALSPAC administrative records.…”
Section: Methodsmentioning
confidence: 99%
“…Antibody tests provided by Una Health and Fortress Diagnostics Ltd. were sent to consenting participants in October 2020. The methodology is described in more detail here 7 . Briefly, 5220 participants were sent testing kits through the reporting a positive result on our antibody test, 55 reported that they did not think they had had COVID-19 in Q3, emphasising the importance of not relying on symptoms and self-report only.…”
Section: Serology Resultsmentioning
confidence: 99%
“…Self-report data Online questionnaires were completed by participants in March (Q1), May (Q2) and October 2020 (Q3) [5][6][7] . The following questions were asked: Using [1] we applied the algorithm developed by Menni et al 10 for each set of monthly data to determine whether a participant was a 'probable' case in that month 11 .…”
Section: Baselinementioning
confidence: 99%
“…The update to the datasets obtained from our previous questionnaires [7][8][9] is described here, together with any variables that have been derived using multiple sets of questionnaire data. We also present a brief assessment of the factors associated with returning the fourth COVID questionnaire, but not any of the previous three, in order to explore who these 'new' participants are.…”
Section: Introductionmentioning
confidence: 99%